Strengthening Enforcement in Unemployment Insurance. A Natural Experiment - Amelie Schiprowski; Patrick Arni (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Imposing benefit cuts to job seekers who do not comply with rules and requirements has become a commonly used enforcement device in unemployment insurance (UI) systems. This paper provides first estimates of how non-compliant job seekers react when confronted with a stricter enforcement regime. We exploit an administrative reform which induced a sharp and unanticipated increase in the probability of receiving a benefit cut in response to the failure of documenting job search effort. Our difference-in-difference framework uses as a control group job seekers with other types of non-compliances, whose enforcement rules stayed constant. We find that the probability of job finding within the three months following non-compliance detection increases by 5 p.p. in reaction to the reform. This effect is however purely driven by exits to unstable jobs. Increased enforcement strictness thus appears to pressure job seekers into accepting job matches of lower quality. Estimating the effects on post-unemployment earnings is work in progress.
Keywords: J65; J64; J58; 330